'Incessant' tachycardias in Wolff-Parkinson-White syndrome. I: Initiation without antecedent extrasystoles or PR lengthening, with reference to reciprocation after shortening of cycle length. Issue 9 (September 1976) - Krikler, D; Curry, P; Attuel, P; Coumel, P
Abstract : In 6 patients with the Wolff-Parkinson-White (WPW) syndrome, repetitive, almost continuous (incessant) reciprocating atrioventricular (AV) tachycardia has been shown to arise when the sinus cycle length was shortened to a critical point, at which unidirectional block occurred without the classical feature of PR prolongation. Though this phenomenon superficially resembles an aspect of chronic intranodal reciprocating tachycardia of children, basic differences can be identified. It was encountered more frequently in younger subjects; the only patient over 45 developed the arrhythmia as a complication of therapy. This incessant mechanism may explain some cases in which antiarrhythmic treatment does not control reciprocating tachycardia in the WPW syndrome, but such a mechanism can also occur spontaneously.